Clinical characteristics of chronic lymphocytic leukemia occurring in chornobyl cleanup workers. Issue 2 (25th January 2016) - Finch, Stuart C.; Dyagil, Irina; Reiss, Robert F.; Gudzenko, Nataliya; Babkina, Nataliya; Lyubarets, Tatiana; Bebeshko, Volodymyr; Romanenko, Anatoly; Chumak, Vadim V.; Bouville, Andre; Hatch, Maureen; Little, Mark P.; et al.
Abstract: The recently demonstrated radiation‐induction of chronic lymphocytic leukemia (CLL) raises the question as to whether the amount of radiation exposure influences any of the clinical characteristics of the disease. We evaluated the relationship between bone marrow radiation doses and clinical characteristics and survival of 79 CLL cases diagnosed during 1986–2006 in a cohort of 110 645 male workers who participated in the cleanup work of the Chornobyl nuclear accident in Ukraine in 1986. All diagnoses were confirmed by an independent International Hematology Panel. Patients were followed up to the date of death or end of follow‐up on 31 October 2010. The median age at diagnosis was 57 years. Median bone marrow dose was 22.6 milligray (mGy) and was not associated with time between exposure and clinical diagnosis of CLL (latent period), age, peripheral blood lymphocyte count or clinical stage of disease in univariate and multivariate analyses. Latent period was significantly shorter among those older at first exposure, smokers and those with higher frequency of visits to the doctor prior to diagnosis. A significant increase in the risk of death with increasing radiation dose was observed ( p = 0.03, hazard ratio = 2.38, 95% confidence interval: 1.11, 5.08 comparing those with doses ≥22 mGy to doses <22 mGy). After adjustment for radiation dose, survival of CLL cases was significantly shorter among those with younger age at first exposure, higher peripheral blood lymphocyte count, more advanced clinical stage of disease and older age at diagnosis (all p < 0.05). This is the first study to examine association between bone marrow radiation doses from the Chornobyl accident and clinical manifestations of the CLL in Chornobyl cleanup workers. The current study provides new evidence on the association of radiation dose and younger age at first radiation exposure at Chornobyl with shorter survival after diagnosis. Future studies are necessary with more cases in order to improve the statistical power of these analyses and to determine their significance. Copyright © 2016 John Wiley & Sons, Ltd.